Persepsi Siswa terhadap Variasi Mengajar Guru Pendidikan Agama Islam di SMK Telkom Pekanbaru - Sariah Sariah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Variation skills are one of the skills a teacher must possess. These skills include variation in teaching (teaching style), interaction patterns of learning and variation in the use of learning media. These three variations, if implemented, will create an effective learning atmosphere and can create good interaction and communication between teacher and students and provide students with positive perceptions of the teacher. To improve this, the teacher must improve teaching variation skills, this will increase students' positive perceptions of the teacher. Based on these thoughts, this paper is an effort to trace students' perceptions of the variation of teaching religious teachers at SMK Telkom Pekanbaru. This discussion was conducted using a descriptive approach by applying questionnaire and documentation techniques. The results of this discussion indicate the level of student perceptions of the variation of teaching religious teachers at SMK Telkom Pekanbaru is categorized quite well with the percentage obtained at 65.96%.